Preventing infant and child morbidity and mortality due to maternal depression. (October 2016) - Surkan, Pamela J.; Patel, Shivani A.; Rahman, Atif
Abstract : This review provides an overview of perinatal depression and its impacts on the health of mothers, their newborns, and young children in low- and middle-income countries (LMICs). We define and describe the urgency and scope of the problem of perinatal depression for mothers, while highlighting some specific issues such as suicidal ideation and decreased likelihood to seek health care. Pathways through which stress may link maternal depression to childhood growth and development (e.g., the hypo-pituitary axis) are discussed, followed by a summary of the adverse effects of depression on birth outcomes, parenting practices, and child growth and development. Although preliminary studies on the association between maternal depressive symptoms and maternal and child mortality exist, more research on these topics is needed. We describe the available interventions and suggest strategies to reduce maternal depressive symptoms in LMICs, including integration of services with existing primary health-care systems. Highlights: Perinatal mental health is an urgent issue in LMICs. It is a fundamental upstream cause of a variety of adverse maternal and child outcomes. Integration of mental and primary health care is needed in low-resource settings.